Chronic Lactiferous Fistula: A Case Report - S, Sharini; AK, Norie; H, Haida (IIUM Medical Journal Malaysia, 2017)
Lactiferous or milk fistula is a tract between the skin and lactiferous duct. Chronic lactiferous duct is uncommon and generally formed during lactating period. It commonly result from complication of the surgical intervention, such as excision biopsy of breast mass or incision and drainage (I&D) for breast abscess. We reported a case of chronic lactiferous fistula secondary to previous I&D for breast abscess in 31 year old lactating woman.